A synergistic approach for regional particle pollution tracking using multiple mobile vehicle-based lidars. (15th July 2020) - Lv, Lihui; Xiang, Yan; Zhang, Tianshu; Chai, Wenxuan; Liu, Wenqing
Abstract: The air pollution in China has presented remarkable regional and complex characteristics, and particle explosive growth events happened frequently. In view of the domestic situation, a new synergistic approach, which could detect particle pollution over large area rapidly, is urgently needed. A rapid detection approach based on multiple mobile vehicle-based lidar systems is proposed to meet the needs of regional particle pollution observation in this paper. Take the Jing-Jin-Ji (the abbreviation of Beijing-Tianjin-Hebei) area for example, the methodology and practice of the rapid synergistic approaches with three sets of mobile vehicle-based lidars are presented. On the premise of synergistic observation scheme design and data quality control, we conducted a synergistic observation of aerosol in Jing-Jin-Ji area on 4 November 2017. Then the spatial distribution and transport characteristics of particle pollution in this area are discussed. The synergistic observation results show that high aerosol extinction was observed on the southwest pathway in this case. Furthermore, the spatial distribution characteristics of aerosol optical depth and boundary layer height were analyzed in this study. The comprehensive analysis of synergistic observation results, backward trajectories, and near-surface concentration of PM2.5 based on in situ instrument further illustrated the transport from the southwest pathway strongly affects air quality. The synergistic approach based on multiple mobile vehicle-based lidars provides an effective approach on regional pollution tracking and characterizing within hours. Highlights: A synergistic approach for regional pollution tracking based on multiple mobile vehicle-based lidars was presented. Characteristics of the regional distribution of aerosol particles in Jing-Jin-Ji were observed. The significant AOD and BLH was found together on the southwest pathway in the early stage of haze development.